2013
DOI: 10.1371/journal.pone.0061144
|View full text |Cite
|
Sign up to set email alerts
|

A Frameshift Mutation in the Cubilin Gene (CUBN) in Border Collies with Imerslund-Gräsbeck Syndrome (Selective Cobalamin Malabsorption)

Abstract: Imerslund-Gräsbeck syndrome (IGS) or selective cobalamin malabsorption has been described in humans and dogs. IGS occurs in Border Collies and is inherited as a monogenic autosomal recessive trait in this breed. Using 7 IGS cases and 7 non-affected controls we mapped the causative mutation by genome-wide association and homozygosity mapping to a 3.53 Mb interval on chromosome 2. We re-sequenced the genome of one affected dog at ∼10× coverage and detected 17 non-synonymous variants in the critical interval. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 21 publications
2
31
0
3
Order By: Relevance
“…However, it works against fine-mapping efforts, as many marker alleles cosegregate with the causal variant. Fortunately, as the costs of conducting whole-genome sequencing (WGS) decrease, platform performance improves, and the tools needed to reliably call variants are refined, fine mapping to identify the causal genetic underpinnings of traits and diseases is becoming less laborious (Frischknecht et al 2013, Karlsson et al 2013, Owczarek-Lipska et al 2013a, Schoenebeck et al 2012). …”
Section: Genetic Approaches To Mapping Canine Traits and Diseasesmentioning
confidence: 99%
“…However, it works against fine-mapping efforts, as many marker alleles cosegregate with the causal variant. Fortunately, as the costs of conducting whole-genome sequencing (WGS) decrease, platform performance improves, and the tools needed to reliably call variants are refined, fine mapping to identify the causal genetic underpinnings of traits and diseases is becoming less laborious (Frischknecht et al 2013, Karlsson et al 2013, Owczarek-Lipska et al 2013a, Schoenebeck et al 2012). …”
Section: Genetic Approaches To Mapping Canine Traits and Diseasesmentioning
confidence: 99%
“…Analogous to the recent identification of the causative mutation in cobalamin‐deficient border collies,9 a whole genome resequencing approach was used in the described beagles. Stored blood samples (EDTA) from case 1 and a paraffin‐embedded formalin‐fixed liver sample from case 2 were used to isolate genomic DNA.…”
Section: Genetic Studiesmentioning
confidence: 99%
“…In dogs, primary cobalamin malabsorption, which is analogous to IGS in humans, has been reported in young Australian Shepherds,3 a Beagle,4 Border Collies,5, 6, 7 and Giant Schnauzers 8. The genetic defects in affected Border Collies and Beagles recently have been identified as 2 independent mutations in the CUBN gene 9, 10. Similar to human patients, dogs typically present at a young age with inappetence, weakness, and failure to thrive 4, 5, 6, 8, 11.…”
mentioning
confidence: 99%
“…Genotyping performed on this sample using a previously described method (Owczarek‐Lipska et al . ) revealed that the dog carried the CUBN:c.786delC mutation in a homozygous state, confirming hereditary cobalamin deficiency (Drögemüller et al . ).…”
Section: Case Historymentioning
confidence: 73%
“…, Owczarek‐Lipska et al . ). Similar to humans, dogs typically present at a young age with inappetence, weakness and failure to thrive.…”
Section: Introductionmentioning
confidence: 97%